Sport Administrators' Perspectives on Advancing Safe Sport - Gurgis, Joseph John; Kerr, Gretchen A. (Frontiers in Sports and Active Living, 2021)
Numerous international high-profile cases of athlete abuses have led to efforts to advance what has been termed “Safe Sport.” Sport and coaching organisations are urgently designing and implementing policies, procedures and programmes to advance a culture of safe sport. However, we posit that these endeavours are occurring without a conceptual framework about what constitutes safe sport or how to achieve it. Without a consistent conceptual framework for safe sport, prevention and intervention initiatives may not be fully realised. As such, the purpose of the study was to explore sport administrators' perspectives of how to advance safe sport. Given the leadership positions sport administrators hold, understanding their perspectives may be helpful in informing a framework to guide the development and implementation of safe sport strategies. Using a constructivist grounded theory approach, semi-structured interviews were conducted with 13 sport administrators from different sport and coaching organisations to elicit views on how best to advance safe sport. The findings indicated that a multi-faceted approach embracing multiple advancement strategies was reportedly essential for progressing safe sport. Specifically, the sport administrators recommended that sport organisations establish a universal framework of safe sport, design and implement education, implement and enforce policies, establish independent monitoring and complaint mechanisms and conduct research to ensure that advancement strategies are current and applicable. The participants suggested that these advancement strategies are necessary to evolve sport from a culture that embraces hegemonic masculine narratives, interpersonal violence and controlling coach–athlete relationships, to a culture of sport that extends the safe sport focus beyond the prevention of harm to the promotion of positive values and human rights. The findings were interpreted through a safeguarding lens to propose a framework for achieving safeguarding sport, defined by the prevention of harm and the promotion of positive values in sport.